(untitled) - Froggatt, Colin; Froggatt, C. D (Singapore, 1991)
The development in our understanding of symmetry principles is reviewed. Many symmetries, such as charge conjugation, parity and strangeness, are no longer considered as fundamental but as natural consequences of a gauge field theory of strong and electromagnetic interactions. Other symmetries arise naturally from physical models in some limiting situation, such as for low energy or low mass. Random dynamics and attempts to explain all symmetries — even Lorentz invariance and gauge invariance — without appealing to any fundamental invariance of the laws of nature are discussed. A selection of original papers is reprinted
Keywords: Particles (Nuclear physics); Standard model (Nuclear physics); Symmetry (Physics); Đối xứng; Mô hình chuẩn (Vật lý hạt nhân); Hạt (Vật lý hạt nhân)